Prototype of the S-band buncher for the VEPP-5 preinjector - Antoshin, A.V.; Podlevskih, V.V.; Tarnetsky, V.V. (Вопросы атомной науки и техники, 1999)
The buncher system of the VEPP-5 preinjector consists of two subharmonic cavities at operating frequency of 180 MHz (the 16-th subharmonic of the operating frequency f₀ = 2856 MHz), S-band buncher, and the first accelerating structure with the operating frequency of 2856 MHz. By now a prototype of the buncher, presented in the paper, has been manufactured. Measurements carried out are in a good agreement with simulation results. A new version of the buncher, which will allow us to control not only an amplitude, but also phase ratio in accelerating cavities is under development now.